2012
DOI: 10.5539/gjhs.v4n5p120
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Anxiety in Stutterers through the Association between “Purpose in Life/Ikigai” and Emotions

Abstract: The prefrontal lobe is more evolved in humans than in other mammals. The functioning of human prefrontal lobes promotes an innate need to establish a meaningful life, often referred to as “Purpose in life (PIL)/ikigai.” PIL/ikigai and the prefrontal lobe psychologically and physiologically, respectively, shape ambition, regulate the development of emotions and integrate psychological events. PIL/ikigai contributes to both a reduction in the anxiety caused by a need for approval from others and the stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The result indicated that achievement motive had greater effects on the support-related purpose in life for elderly persons than on social participation and role expectation. In previous studies, purpose in life has been associated with well-being and life satisfaction ( Bronk et al, 2009 ; Ryff, 1989 ; Ryff & Keyes, 1995 ), and has had an effect on restraining mortality risk, anxiety, and stress ( Boyle et al, 2009 ; Ishida, 2012 ). Also, purpose in life is future-orientated and goal-orientated ( Bronk et al, 2009 ), and involves the individual’s intention to achieve something ( Demura & Sato, 2006 ; Nomura, 2005 ); therefore, enhancing purpose in life may be the goal for the rehabilitation of elderly persons.…”
Section: Discussionmentioning
confidence: 95%
“…The result indicated that achievement motive had greater effects on the support-related purpose in life for elderly persons than on social participation and role expectation. In previous studies, purpose in life has been associated with well-being and life satisfaction ( Bronk et al, 2009 ; Ryff, 1989 ; Ryff & Keyes, 1995 ), and has had an effect on restraining mortality risk, anxiety, and stress ( Boyle et al, 2009 ; Ishida, 2012 ). Also, purpose in life is future-orientated and goal-orientated ( Bronk et al, 2009 ), and involves the individual’s intention to achieve something ( Demura & Sato, 2006 ; Nomura, 2005 ); therefore, enhancing purpose in life may be the goal for the rehabilitation of elderly persons.…”
Section: Discussionmentioning
confidence: 95%
“…The phrase "purpose of life" originates in 19th century European existential philosophy. İkigai, as a term, traces back to 14th century Japan [6,7]. Both purpose in life and İkigai are psychologically related to purpose and ambition in life.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of social relations and support mechanisms have an impact on behaviors (Hunter et al, 2019 ; Labrague, 2021 ). Many studies have focused on factors such as social support and ikigai, predicting their positive impact on negative behaviors (Callaghan & Morrissey, 1993 ; Ghaderi Rammazi et al, 2018 ; Ishida, 2012b ; Kaplan et al, 1977 ; Schwarzer & Leppin, 2016; Seko & Hirano, 2021 ; Steger & Kashdan, 2009 ). The role of social support as preventive and protective is important in terms of social and behavioral problems (Schwarzer & Leppin, 1991 ).…”
Section: Introductionmentioning
confidence: 99%